2020
DOI: 10.1063/5.0023077
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low magnetic damping in epitaxial Li0.5Fe2.5O4 thin films

Abstract: The realization of more energy efficient nanomagnetic information devices relies on the existence of magnetic insulators capable of supporting pure spin currents in the absence of a dissipative charge current. Currently, there is a limited number of thin-film magnetic insulators with low magnetic damping. Li0.5Fe2.5O4 (LFO) is well known to possess the lowest damping among the bulk spinel structure oxides, but, thus far, LFO thin films have not lived up to these expectations. Here, we demonstrate low magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Sample deposition and fabrication. Epitaxial Li 0.5 Al 47,48 . After the growth of the ferrite thin films of various thicknesses and compositions, Py(5 nm)/Pt(5 nm) bilayers are deposited on LAFO and LFO via a Kurt Lester magnetron sputtering system at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Sample deposition and fabrication. Epitaxial Li 0.5 Al 47,48 . After the growth of the ferrite thin films of various thicknesses and compositions, Py(5 nm)/Pt(5 nm) bilayers are deposited on LAFO and LFO via a Kurt Lester magnetron sputtering system at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, multiferroic nanocomposite is an important class of nanocomposite that have become in attention because of their promising applications such as in energy conversion, fuel cells, storage, shape memory actuation and solidstate refrigeration, next-generation spintronics devices or multiple state memory elements, and transducers with magnetically modulated piezoelectricity [1][2][3][4][5][6][7]. In particular, biferroic is a class of multiferroics that shows the simultaneous ferroelectric and ferromagnetic order parameters [8]. Generally, the concept of multiferroic stands for the presence of an interaction between the ferroelectric and ferromagnetic subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…The ferroelectric behavior of BTO is arising from the crystal asymmetry which is associated with the displacement of Ti ion from its body-centered positions in the crystal lattice [11,12]. Zheng et al reported that BTO NPs can enhance the multifunctional properties of Li 0.5-Fe 2.5 O 4 [8].…”
Section: Introductionmentioning
confidence: 99%
“…13 LiFe 5 O 8 thin films have been prepared by various physical and chemical vapor deposition techniques and their structural and magnetic properties have been reported by a few research groups. [14][15][16] Detailed studies on the temperature and frequency dependent electrical properties and the effect of thickness on the optical band gap tuning properties and controlling the band edge parameters through oxygen vacancy filling in LiFe 5 O 8 thin films have not been performed in the literature. In the present work, we have deposited LiFe 5 O 8 thin films on Al 2 O 3 (0001) substrates by the pulsed laser deposition method and explored the thickness-dependent optical, electronic and electrical properties correlated with the band edge parameters.…”
Section: Introductionmentioning
confidence: 99%
“…13 LiFe 5 O 8 thin films have been prepared by various physical and chemical vapor deposition techniques and their structural and magnetic properties have been reported by a few research groups. 14–16…”
Section: Introductionmentioning
confidence: 99%